Flash flood and debris flow in the Harihara River, Kyushu, Japan (Journal of Nepal Geological Society, 2000)
The flash flood and debris flow after a heavy rainfall wiped out a village of southern Japan on the tragic midnight of 10 July 1997, and a great loss of property and lives took place in this ill-fated incident. After the heavy rainfall, the debris flow induced by a sudden flash flood took 21 lives in Southern Kyushu. Detailed field investigation, in situ survey, electrical survey, and hydrogeological analyses were conducted to find out the triggering factors of the disaster.The main factors of this disaster were a hidden fault and the perched groundwater. Moving soil mass downhill into the agricultural pond had triggered the flash flood. The details of sequential disaster events as perceived from the observation and analyses are presented in this paper.